Improving run-time stability with aerosol jet printing using a solvent add-back bubbler - Wadhwa, Arjun; Cormier, Denis; Williams, Scott (Journal of Print and Media Technology Research, 2023)
Aerosol jet printing is a non-contact process capable of printing on conformal and flexible surfaces. Aqueous or solvent nano-inks are pneumatically atomized under nitrogen. The atomizing gas flow through the atomization cup leads to evaporation and removal of volatile solvent(s). As the ink solid loading fraction increases with the loss of solvent during atomization, the rheological changes eventually lead to instabilities in print output. A potential solution to this problem is to moisten the incoming atomizing gas with a solvent add-back system. In this study, neat co-solvent solutions of ethanol and ethylene glycol at 85 : 15 and 30 : 70 mixing ratios were atomized using nitrogen flow rates ranging from 600 to 1 000 cm3 ∙ min−1 (ccm, cubic centimeters per minute). It was observed that ethanol, being the more volatile solvent, was depleted from the neat solution at a much higher rate than ethylene glycol. When nitrogen gas was passed through a bubbler prior to atomization, an excessive amount of ethanol was returned to the neat solution. The solvent loss rate from an ethanol rich neat solution (80 %) was higher compared to an ethylene glycol rich neat solution. Perfecting the solvent add-back rate to an ink will enable longer print runs in a manufacturing environment.